The characteristics and perioperative outcomes of children with orofacial clefts managed at an academic hospital in Johannesburg, South Africa - Prosperity A. Sithole; Palesa Motshabi-Chakane; Michel K. Muteba (BMC, 2022)
Abstract Background Orofacial clefts (OFCs) are the commonest congenital anomalies of the head and neck. Their aetiology is multifactorial, and prevalence has a geographical variation. This study sought to describe OFC cases that presented for surgery. Objectives The study aimed to describe the preoperative characteristics, concomitant congenital anomalies and perioperative outcomes of children presenting for cleft repair surgery over a 5-year period at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods A retrospective descriptive record review for children under the age of 14 years who presented for cleft repair surgery at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) during a 5-year period, from 1 January 2014 to 31 December 2018. Descriptive and comparative statistics were used to report the results. Results A total of 175 records were included in the study. The median (IQR) age was 11 (6-27) months, with a predominance of males 98 (56%). Most of the children had cleft lip and palate (CLP) 71(41%). The prevalence of concomitant congenital anomalies was 22%, emanating mostly from head and neck congenital anomalies. Nine syndromes were identified in 15 children with syndromic clefts. Twenty-nine percent of children were underweight for age. There were 25 anaesthetic related complications, commonly airway related. Six children with complex multiple congenital anomalies were admitted in the intensive care unit postoperatively. No mortalities were recorded. Conclusion Majority of children with orofacial clefts underwent cleft repair surgery without serious complications and intensive care unit admission. Only six children were diagnosed with significant anomalies needing intensive care management.